Computational intelligence techniques and their applications to software engineering problems - Bansal, Ankita (Boca Raton : CRC Press, 2021)
"This book focuses on computational intelligence approaches as applicable in varied areas of software engineering such as software requirement prioritization, cost estimation, reliability assessment, defect prediction, maintainability and quality prediction, size estimation, vulnerability prediction, test case selection and prioritization, and so forth. The concepts of expert systems, case-based reasoning, fuzzy logic, genetic algorithms, swarm computing, rough sets are introduced with their application in software engineering. The field of knowledge discovery is explored using neural networks and data mining techniques by discovering the underlying and hidden patterns in software data sets"--
Implementation of artifical intelligence techniques for improving software engineering / Sushma Malik, Monika Arora, Anamilka Rana and Mamta Bansal -- Software effort estimation : machine learning vs. hybrid algorithms / Wasiur Rhmann.
OCLC-licensed vendor bibliographic record.
Keywords: Software engineering -- Data processing; Computational intelligence; COMPUTERS / Machine Theory; COMPUTERS / Programming / Software Development; TECHNOLOGY / Electricity